Formulation and Evaluation of Water Fraction Hair tonic Containing Flavonoids from Ethanolic Extract of Green Tea Leaves (Camellia sinensis L.) - Elsa Fitria Apriani; Adik Ahmadi; Vini Noviani (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Hair growth tonics containing herbal and synthetic ingredients have been developed to overcome hair loss and baldness. Advanced technological developments made many Indonesians prefer to use herbal products compared to synthetic products due to their fewer side effects. Green tea leaves (Camellia sinensis L.) is a plant believed to increase hair growth rates due to its flavonoid compounds. The purpose of this study is to formulate hair tonic from water fraction ethanolic extract green tea leaves, to look at the activity of hair growth-promoting, and also to look at physical stability, irritation tests, and microbial contamination. The positive control used is 2% Minoxidil. The hair growth activity test was carried out by applying a hair tonic to rabbits. Hair growth measurement data were statistically tested by the ANOVA test. The formulated green tea leaves tonic met the physical properties test. The tonic produces similar growth activities with the positive control (significance difference (p> 0.05)). In addition, the tonic does not have a skin irritation effect on rabbit skin and is free from bacteria.